Financial crisis and bank executive incentive compensation - Bhagat, Sanjai; Bolton, Brian (Journal of Corporate Finance, 2014)
We study the executive compensation structure in 14 of the largest U.S. financial institutions during 2000–2008. We focus on the CEO's purchases and sales of their bank's stock, their salary and bonus, and the capital losses these CEOs incur due to the dramatic share price declines in 2008. We consider three measures of risk-taking by these banks. Our results are mostly consistent with and supportive of the findings of Bebchuk, Cohen and Spamann (2010), that is, managerial incentives matter — incentives generated by executive compensation programs are correlated with excessive risk-taking by banks. Also, our results are generally not supportive of the conclusions of Fahlenbrach and Stulz (2011) that the poor performance of banks during the crisis was the result of unforeseen risk. We recommend that bank executive incentive compensation should only consist of restricted stock and restricted stock options — restricted in the sense that the executive cannot sell the shares or exercise the options for two to four years after their last day in office. The above incentive compensation proposal logically leads to a complementary proposal regarding a bank's capital structure, namely, banks should be financed with considerably more equity than they are being financed currently.